Un heroe sen tempo: 20 anos de cultura galega sen Reimundo Patiño - Gutiérrez Failde, Xosé Lois (Madrygal. Revista de Estudios Gallegos, 2005)
This article review the aesthetic project of Reimundo Patiño when take place the 20th aniversary of his death.
Keywords: Border; aesthetic project; historical edge; art; ideology